Seismic Site Classification Using the Multichannel Analysis of Surface Waves Method - Syamsuddin, Erfan; Aswad, Sabrianto; Assegaf, Muhammad Alimuddin Hamzah; Rasimeng, Syamsurijal; Sakka, Sakka; Syamsuddin, Syamsuddin; Nasri, Muhammad; Syihab, Mufly Fadla (POSITRON, 2022)
The soil has a variety of qualities that affect its ability to support the weight of a structure. One of these features is soil stiffness, which can be determined using the surface wave method to prevent soil collapse. Multichannel Analysis of Surface Waves (MASW) is one of the non-invasive methodologies used in this study to investigate subsurface structures in North Sumatra, Indonesia. This method utilizes the dispersion properties of Rayleigh waves, producing a dispersion curve to get the shear wave velocity (Vs) through inversion. The shear wave velocity can be used to examine the soil stiffness qualities. The dispersion curve explains the relationship between shear wave velocity and depth, which can subsequently be used as a site class parameter. This survey uses three lines with one shot for each line which uses thirty geophones. The seismic source used is a gun with the type M16.38 Cal. Each line consists of 30 geophones with a distance of 5 m. The entire track is 160 m long and lasts for 2048 seconds with a sampling rate of 0.00025 seconds. The average shear wave velocity measured at three measurements was 372.5 m/s on line P1, 347.1 m/s on line P2A, and 311.0 m/s on line P2B, respectively. Overall, the soil classification on the P1 line is class C, and the P2A and P2B lines are class D, which is suitable for development planning areas.